Helicobacter pylori-possible role as biomarker for oral cancer - Archana A Gupta; Supriya M Kheur; Mohit Kheur; Shraddha R Saner (Wolters Kluwer Medknow Publications, 2014)
Oral cancer is the most common cancer diagnosed in Indian men and is the leading cause of cancer deaths. Amongst other causes infections with Helicobacter pylori is an emerging cause of oral squamous cell carcinoma. There is still confusion in the route of transmission and the exact etiopathogenesis of H. pylori associated oral cancer. Knowledge of the microbiology and immunology of H. pylori is important to prevent its spread and may be useful in identifying high-risk populations, especially in areas that have high rates of gastric lymphoma, gastric cancer, and gastric ulcer. This paper presents an overview of the important aspects of H. pylori.